Optimization Analysis of Controlled Blasting for Passing through Houses at Close Range in Super-Large Section Tunnels - Zhanping Song; Jianchao Mao; Xiaoxu Tian; Yuwei Zhang; Junbao Wang (Shock and Vibration)
According to the on-site vibration velocity monitoring and peak vibration velocity prediction, it is found that the maximum vibration velocity generated by the existing Dizong blasting scheme does not meet the requirements of the maximum allowable vibration velocity of houses. Therefore, the existing blasting scheme is optimized by reducing the maximum single-segment charge and a variety of damping measures such as multistage duplex wedge groove, adding damping hole, and millisecond blasting. In addition, the blasting data before and after optimization are analyzed and compared by wavelet (packet) technology. The results show that the optimized blasting main frequency domain is increased to 50∼150 Hz and the maximum vibration intensity value is reduced by 79.8%. Based on the time-energy analysis, the maximum energy value is reduced by 67.75% compared with the original scheme, and the dominant energy of the original scheme is reduced by 97.81%, 71.49%, 82.44%, 95.93%, and 93.03%, respectively, after optimization. The maximum vibration velocity generated by the optimized blasting scheme construction is 1.12 cm/s, which is less than the maximum allowable vibration velocity of the building of 1.2 cm/s, which meets the maximum allowable vibration velocity requirements of the building. The optimized blasting scheme realizes the safe and rapid construction of the two steps of the Dizong tunnel, which can provide a reference for similar engineering construction in the future.